2020
DOI: 10.1080/17461391.2020.1790670
|View full text |Cite
|
Sign up to set email alerts
|

The intraocular pressure response to lower‐body and upper‐body isometric exercises is affected by the breathing pattern

Abstract: erD tes¡ us nd edondoD fetriz nd erezEgstillD elejndro nd uoulierisD qeorgeEelex nd tim¡ enezD imundo nd qriEmosD emdor @PHPIA 9he introulr pressure response to lowerEody nd upperEody isometri exerises is 'eted y the rething ptternF9D iuropen journl of sport sieneFD PI @TAF ppF VUWEVVTF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…Regarding IOP, Najmanová et al (2019) [17] found a negative relationship between oxygen saturation and IOP levels during extreme normobaric hypoxia exposure. Also, the manipulation of the breathing pattern adopted during resistance training has demonstrated to alter the IOP behavior, observing a heightened IOP rise when the interchange of gases is compromised [11,12]. Based on this, it is plausible that the alteration of gas concentration and the increased breathing resistance with face masks are responsible for the higher IOP values obtained in the FFP2/N95 mask condition, although further studies are needed to determine the physiological mechanisms responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding IOP, Najmanová et al (2019) [17] found a negative relationship between oxygen saturation and IOP levels during extreme normobaric hypoxia exposure. Also, the manipulation of the breathing pattern adopted during resistance training has demonstrated to alter the IOP behavior, observing a heightened IOP rise when the interchange of gases is compromised [11,12]. Based on this, it is plausible that the alteration of gas concentration and the increased breathing resistance with face masks are responsible for the higher IOP values obtained in the FFP2/N95 mask condition, although further studies are needed to determine the physiological mechanisms responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…The execution of low-intensity endurance exercise (e.g., walking, jogging, or cycling) has an IOP-lowering effect, which is highly recommended in glaucoma patients [9,10]. However, recent investigations suggest that restricting the exchange of gases during resistance training exercises promotes an acute IOP rise [11,12]. In addition, there are claims that face masks reduce cardiopulmonary exercise capacity and increase subjective breathing resistance, with these effects being more pronounced with FFP2/N95 in comparison to surgical masks [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vera et al advised the participants to keep a constant pattern of breathing during the hold while our participants were allowed to perform the test with the regular breathing technique. 49 50 Here, the participants were performing lifts that were very close to their maximal effort, and the chances of failure (of the rep) were high. So long that the participants performed the repetition with good form, they were not told how to breathe during the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the contrary, the execution of resistance training against heavy loads provokes an acute IOP rise, [19][20][21][22][23] and this effect is exacerbated when the interchange of gases is compromised. 24,25 In the same line, the exposure to hypoxia and hypercapnia conditions has been shown to induce a significant IOP rise. 26,27 Remarkably, a recent study showed that using a FFP2 mask counteracts the IOP lowering-effect of low-intensity aerobic exercise on glaucoma patients.…”
mentioning
confidence: 91%